2017
DOI: 10.1042/bsr20160446
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between serum S100β protein levels and cognitive dysfunction in patients with cerebral small vessel disease: a case–control study

Abstract: The present study was designed to explore the correlation between serum S100β levels and cognitive dysfunction in patients with cerebral small vessel disease (SVD). A total of 172 SVD patients participated in the study, and they were assigned to patients with no cognitive impairment (NCI group) and those with vascular cognitive impairment no dementia (VCIND group). In total, 105 people were recruited into the normal control group. Serum S100β protein level was detected by ELISA. A receiver operating characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
3
12
0
2
Order By: Relevance
“…However, the cognitive implications of S100B are not limited to T2DM: studies have shown that this protein is involved in cognitive impairment in a variety of diseases, including cerebral small vessel disease and AD [9,48]. Cerebral small vessel disease (CSVD) is an age-related disease affecting the small blood vessels of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cognitive implications of S100B are not limited to T2DM: studies have shown that this protein is involved in cognitive impairment in a variety of diseases, including cerebral small vessel disease and AD [9,48]. Cerebral small vessel disease (CSVD) is an age-related disease affecting the small blood vessels of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Davidson et al [ 18 ] showed that carrying the APOE- ε 4 allele was associated with an increased risk of vascular dementia. Treves et al [ 19 ] showed that the APOE- ε 4 allele frequency was highest in AD patients, followed by VCIND patients, and then the control group. Hsiung et al [ 20 ] showed that VCIND patients and APOE- ε 4 allele carriers are more common in advanced disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…The Mini‐Mental State Evaluation (Chinese version, full mark is 30) and Montreal Cognitive Assessment Scale (Chinese version, full mark is 30) were performed by specialised personnel of research team. According to the newly published diagnostic criteria and classification of postoperative neurocognitive dysfunction, 12 delayed postoperative neurocognitive recovery was defined as patient in whom scores decreased by more than or equal to 1 standard deviation from preoperative levels on one or two cognitive assessment scales 13‐15 …”
Section: Methodsmentioning
confidence: 99%